Clostridioides (Clostridium) difficile infection burden in Japan: A multicenter prospective study. (December 2019) - Kato, Haru; Senoh, Mitsutoshi; Honda, Hitoshi; Fukuda, Tadashi; Tagashira, Yasuaki; Horiuchi, Hiroko; Chiba, Hiroshi; Suzuki, Daisuke; Hosokawa, Naoto; Kitazono, Hidetaka; Norisue, Yasuhiro; Kume, Hisashi; et al.
Abstract: Clostridioides ( Clostridium ) difficile is the leading cause of healthcare-associated infectious diarrhea in the developed world. Retrospective studies have shown a lower incidence of C. difficile infection (CDI) in Japan than in Europe or North America. Prospective studies are needed to determine if this is due lack of testing for C. difficile or a true difference in CDI epidemiology. A prospective cohort study of CDI was conducted from May 2014 to May 2015 at 12 medical facilities (20 wards) in Japan. Patients with at least three diarrheal bowel movements (Bristol stool grade 6–7) in the preceding 24 h were enrolled. CDI was defined by positive result on enzyme immunoassay for toxins A/B, nucleic acid amplification test for the toxin B gene or toxigenic culture. C. difficile isolates were subjected to PCR-ribotyping (RT), slpA -sequence typing ( slpA -ST), and antimicrobial susceptibility testing. The overall incidence of CDI was 7.4/10, 000 patient-days (PD). The incidence was highest in the five ICU wards (22.2 CDI/10, 000 PD; range: 13.9–75.5/10, 000 PD). The testing frequency and CDI incidence rate were highly correlated (R 2  = 0.91). Of the 146 isolates, RT018/018″ was dominant (29%), followed by types 014 (23%), 002 (12%), and 369 (11%). Among the 15 non-ICU wards, two had high CDI incidence rates (13.0 and 15.9 CDI/10, 000 PD), with clusters of RT018/ slpA -ST smz-02 and 018"/smz-01, respectively. Three non-RT027 or 078 binary toxin-positive isolates were found. All RT018/018" isolates were resistant to moxifloxacin, gatifloxacin, clindamycin, and erythromycin. This study identified a higher CDI incidence in Japanese hospitals than previously reported by actively identifying and testing patients with clinically significant diarrhea. This suggests numerous patients with CDI are being overlooked due to inadequate diagnostic testing in Japan. Highlights: A prospective and multi-center study of CDI was conducted in Japan. The incidence rate (7.4/10, 000 patient-days) of CDI was high. The incidence was highest in five ICU wards (22.2 CDI/10, 000 patient-days). PCR-ribotypes 018, 014, 002, and 369 were predominant.